Infantile iatrogenic cushing′s syndrome - Katar Selahattin; Akdeniz Sedat; Ozbek M; Yaramis Ahmet (Wolters Kluwer Medknow Publications, 2008)
High potency or/and extended use of topical corticosteroids, particularly in children, may cause suppression of the hypothalamopituitary-adrenal axis. However, iatrogenic Cushing′s syndrome in infantile age group is very rare and only a few patients have been reported to date in the literature. Here, we report a case of iatrogenic Cushing′s syndrome in a 6-month-old male child whose parents have admitted to the hospital for overweight and skin fragility.